2021
DOI: 10.12962/j20882033.v31i3.6260
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Business Process Management (BPM) Effect towards Data and Information Quality Improvement at Higher Education: A Literature Study

Abstract: Business Process Management (BPM) is a collection of methods, techniques, and tools to optimize organizational performance. In the case of higher education institutions (HEIs), BPM is usually implemented to provide a standard business process. Implementation of Data Governance (DG) is often based on the desire for good Data Quality (DQ), to help an organization carry out its strategies and achieve its objectives. Previous research has proven that DG would improve data quality and safety and trigger a better st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Bührig, Schoorman & Kanckstedt (2018) research revealed that implementing BPM across three campuses of a German university led to processes standardization improvement across campus locations, adoption of best practices, strengthened university's overall team spirit, reduced resistance to using process models and documentation and the development of a BPM-supportive culture. In addition to that, Sujanawati, ER & Wibowo (2021) found that a BPM implementation is a key element for good data governance and consequently a good quality of the data that is obtained through processes in a HEI environment.…”
Section: Theoretical Referencementioning
confidence: 99%
“…Bührig, Schoorman & Kanckstedt (2018) research revealed that implementing BPM across three campuses of a German university led to processes standardization improvement across campus locations, adoption of best practices, strengthened university's overall team spirit, reduced resistance to using process models and documentation and the development of a BPM-supportive culture. In addition to that, Sujanawati, ER & Wibowo (2021) found that a BPM implementation is a key element for good data governance and consequently a good quality of the data that is obtained through processes in a HEI environment.…”
Section: Theoretical Referencementioning
confidence: 99%